Navigating Diagnosis and Treatment of Perianal Condyloma Acuminata in a Bisexual Man: Clinical and Histopathological Insights - Rose Widanti Sugiyanto; Erna Kristiyani; Ketut Kwartantaya (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Condyloma acuminata (CA), caused by Human Papillomavirus (HPV), commonly affects the anogenital region, particularly in young, sexually active individuals. Perianal presentation is less common but significant, often linked to specific sexual practices. Bisexual men represent a unique demographic concerning STI risk factors and require careful assessment. This report details the diagnosis and management of perianal CA in a young bisexual male, emphasizing the diagnostic utility of clinical assessment, sexual history, and histopathology. Case presentation: A 24-year-old Indonesian bisexual male presented with a three-month history of progressively enlarging, asymptomatic perianal nodules. He reported unprotected receptive anal intercourse with a male partner five months prior. Examination revealed multiple skin-colored, verrucous papules in the perianal region. HIV and syphilis screenings were negative. Histopathological examination of a biopsy specimen confirmed CA, showing parakeratosis, papillomatosis, acanthosis, and koilocytosis. Conclusion: Treatment with 90% trichloroacetic acid (TCA) combined with cauterization resulted in significant clinical improvement at one-week follow-up. This case highlights the importance of obtaining a thorough, non-judgmental sexual history, recognizing characteristic lesion morphology, and utilizing histopathology for definitive diagnosis in managing perianal CA, particularly in populations with diverse sexual practices.